2011
DOI: 10.1371/journal.pone.0022948
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA Class I and Class II Alleles and the Outcome of West Nile Virus Infection: An Exploratory Study

Abstract: BackgroundWest Nile virus (WNV) infection is asymptomatic in most individuals, with a minority developing symptoms ranging from WNV fever to serious neuroinvasive disease. This study investigated the impact of host HLA on the outcome of WNV disease.MethodsA cohort of 210 non-Hispanic mostly white WNV+ subjects from Canada and the U.S. were typed for HLA-A, B, C, DP, DQ, and DR. The study subjects were divided into three WNV infection outcome groups: asymptomatic (AS), symptomatic (S), and neuroinvasive disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…Previous studies suggested that these genotypes may modulate antibody responses against EVs (20) and detection of EVs in patients with type 1 diabetes (21). The HLA genotype is also known to modulate the immune response and the course of many other viral infections (22,23). However, such an HLA effect can hardly explain the elevated CVB1 antibodies in patients with type 1 diabetes because the risk effect of CVB1 remained when adjusted for the effect of HLA, and it was seen in Finland where case and control subjects were matched for diabetes-associated HLA genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that these genotypes may modulate antibody responses against EVs (20) and detection of EVs in patients with type 1 diabetes (21). The HLA genotype is also known to modulate the immune response and the course of many other viral infections (22,23). However, such an HLA effect can hardly explain the elevated CVB1 antibodies in patients with type 1 diabetes because the risk effect of CVB1 remained when adjusted for the effect of HLA, and it was seen in Finland where case and control subjects were matched for diabetes-associated HLA genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Certain HLA types appear to be associated with risk of a more severe outcome (HLA-A*68 and C*08) or better resistance to infection (B*40 and C*03) (107). Single nucleotide polymorphism (SNP) studies have detected SNPs in key regulators of immune function, including interferon pathway elements.…”
Section: Genetic Determinants Of Diseasementioning
confidence: 99%
“…The OAS gene cluster activates an important mediator of viral RNA degradation, RNAse L. In humans, sequencing of the OAS gene cluster in 33 individuals with severe WNV infections did not reveal deletions or nonsense mutations; however, 23 single nucleotide polymorphisms (SNPs) in OAS genes were identified that occurred at a higher frequency in symptomatic individuals. In another study, an allele of OAS1 ('A' allele at SNP rs10774671) that enhanced mRNA splicing was more common in WNV-infected individuals than in uninfected controls [76]. That study also tested the function of the SNP on viral replication in an ex vivo model using primary human lymphoid tissue and determined that virus replication varied among the donors and was most efficient among individuals who were homozygous for the 'A' allele [80].…”
Section: Host Determinants Of Flavivirus Encephalitismentioning
confidence: 99%